Strategy for the Development and Implementation of RKS, RKT, and RKAS: A Case Study at SMK Hidayatul Mubtadi’in - Farah Amalia; Sri Wahyuningsih; Moh Tasirun; Istiqomah Istiqomah; Ngurah Ayu Nyoman (JURNAL PENDIDIKAN IPS, 2025)
This study examines the strategy of formulating and implementing data-based planning through the School Development Plan (RKS), Annual Work Plan (RKT), and School Budget Plan (RKAS) at SMK Hidayatul Mubtadi’in Bulusari. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation. The results show that utilizing the Education Report Card (Rapor Pendidikan) helps the school identify urgent issues, design targeted programs, and allocate resources efficiently. Involving stakeholders such as the principal, teachers, treasurer, and school committee fosters collaboration and strengthens ownership of school programs. Data-based planning enhances transparency and accountability in budget and program implementation. However, challenges include low data literacy, limited IT infrastructure, and inconsistent monitoring practices. The study recommends improving data literacy through training, enhancing technological infrastructure, and developing integrated digital systems to support effective and sustainable planning.